IMPACTO DA PRODUÇÃO CIENTÍFICA NA AVALIAÇÃO QUADRIENAL DA CAPES 2013-2016 - UMA ANÁLISE DA ÁREA CIÊNCIAS AGRÁRIAS I - MARTINS, Helgem de Souza Ribeiro; BARBOSA, Josino José (Brazilian Journal of Biometrics, 2019)
Created on July 11, 1951, CAPES develops actions aimed at several lines of action, with emphasis on the support to the Brazilian postgraduate, acting as a funding and regulatory body. Among these lines of action, we highlight the periodic evaluation of postgraduate programs, which is used in the allocation of nancial resources, in which developing programs receive sucient resources for their maintenance and evolution, and consolidated programs are able to seek excellence in scientic research at international level. This work aims to establish a statistical model that allows the assessment of the impact of human resources training and scientic dissemination in the periodic evaluation of CAPES, area of Agricultural Sciences I. The results suggest that, regardless of the scenario, investment in the postgraduate courses, so that the scientic production is leveraged, not only increases the possibilities of ascending to higher CAPES concepts but also acts as a protection factor to the descend to lower concepts, thus guaranteeing a better positioning of postgraduate courses in national and international scope.